2005
DOI: 10.1007/s11064-005-8796-x
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Aconitase is a Transglutaminase 2 Substrate: Transglutamination is a Probable Mechanism Contributing to High-Molecular-Weight Aggregates of Aconitase and Loss of Aconitase Activity in Huntington Disease Brain

Abstract: Transglutaminase activity was found to be present in highly purified non-synaptosomal rat brain mitochondria. A 78-kDa protein in these organelles was shown to be a transglutaminase 2 substrate, and incubation of a non-synaptosomal mitochondrial lysate with transglutaminase 2 yielded high-Mr proteins. The 78-kDa protein was identified as mitochondrial aconitase by MALDI-TOF analysis. Aconitase activity was decreased in a dose-dependent manner when non-synaptosomal rat brain mitochondria were incubated with tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 45 publications
1
34
0
Order By: Relevance
“…In mammals, cytosolic SHMT has been shown to be post-translationally modified by deamidation accompanied by an overall reduced activity of the modified protein (76). A transglutaminase has also been reported in rat mitochondria to reduce ACON1 activity (77), and its activity has been shown to be affected by the ATP/GTP level and disruption of mitochondrial function in humans (78). In chloroplasts, post-translational modifications, such as phosphorylation of the damaged D1 component of the photosystem II (79,80) and polyubiquitination of phytochrome (81), are a requirement for initiating enzymatic protein degradation.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, cytosolic SHMT has been shown to be post-translationally modified by deamidation accompanied by an overall reduced activity of the modified protein (76). A transglutaminase has also been reported in rat mitochondria to reduce ACON1 activity (77), and its activity has been shown to be affected by the ATP/GTP level and disruption of mitochondrial function in humans (78). In chloroplasts, post-translational modifications, such as phosphorylation of the damaged D1 component of the photosystem II (79,80) and polyubiquitination of phytochrome (81), are a requirement for initiating enzymatic protein degradation.…”
Section: Discussionmentioning
confidence: 99%
“…TGase 2 is aberrantly activated in tissues and cells and contributes to neurodegenerative diseases, such as Alzheimer's disease (Citron et al, 2001), Parkinson's disease (Junn et al, 2003;Andrings et al, 2004), neuro-AIDS (Roberts et al, 2003), Huntington's diseases (Kim et al, 2005), hippocampal CA 1 ischemia (Hwang et al, 2009), celiac disease (Naiyer et al, 2008), lupus (Sanchez et al, 2000), autoimmune diseases like rheumatic arthritis (Picarelli et al, 2003), human atherosclerotic coronary arteries (Cho et al, 2008), breast cancers (Park et al, 2009a) and drug resistance in variety of cancer cells Park et al, 2009bPark et al, , 2010. TGase 2 expression is increased in inflammatory diseases such as activation of microglia, a hallmark of brain inflammation (Park et al, 2004), idiopathic inflammatory myopathies (Kim, 2006) and allergic asthma (Hallstrand et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…As stated previously, transglutaminase 2 activity appears to be increased in Huntington´s Disease, leading to huntingtin aggregation and mitochondrial aconitase inhibition (Karpuj et al, 1999;Lesort et al, 1999;Kim et al, 2005). Based on these studies, cystamine, which is a drug capable of inhibiting transglutaminase, was tested as a therapeutic tool to treat Huntington´s Disease.…”
Section: Treatment Options For the Metabolic Deficitmentioning
confidence: 90%
“…These studies reported a reduction in neuronal cell death, improved behavior and prolonged survival in R6/1 X transglutaminase 2 -/-, as compared to R6/1 X transglutaminase 2 +/+ . In addition to affecting huntingtin aggregation, increased transglutaminase 2 activity in Huntington´s Disease caudate may contribute to mitochondrial dysfunction by incorporating aconitase into inactive polymers and dramatically decreasing aconitase activity (Kim et al, 2005).…”
Section: Enzymes Involved In Energetic Metabolism Are Altered In Huntmentioning
confidence: 99%